2020
DOI: 10.13106/jafeb.2020.vol7.no2.21
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Environmental Information Disclosure in Vietnam Listed Companies

Abstract: Environmental pollution and climate change in Vietnam are now becoming a major concern. This situation is increasing the pressure on the companies to improve their social responsibility in production and business activities and disclose the environmental information to meet the requirements of stakeholders. This study investigates the internal and external factors of the company that affects the environmental information disclosure of listed companies on the Vietnam stock market as business sector, firm size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
1
13
0
3
Order By: Relevance
“…Natural mineral and energy resources have distinctive characteristics that require approaches according to their development. The unique features of the mining sector that need to be considered in mining development, among others, are the natural resources of the mine occupying a particular spatial distribution in the earth and the seabed; these are available in limited quantities and are generally non-renewable; its operations involve investment and riskladen activities, which often must be capital and technologyintensive; the mining process has a high potential for environmental change; mineral and energy mining products have a dual function, mainly as a source of industrial raw materials and energy, both for domestic and export needs; and the mining business is able to play a role as the prime mover and spearhead of regional development, in addition to its role in fulfilling the livelihoods of the wider community (Hidjaz, 2019;Nguyen et al, 2020;Nguyen, 2020).…”
Section: Mining Activities In Indonesiamentioning
confidence: 99%
“…Natural mineral and energy resources have distinctive characteristics that require approaches according to their development. The unique features of the mining sector that need to be considered in mining development, among others, are the natural resources of the mine occupying a particular spatial distribution in the earth and the seabed; these are available in limited quantities and are generally non-renewable; its operations involve investment and riskladen activities, which often must be capital and technologyintensive; the mining process has a high potential for environmental change; mineral and energy mining products have a dual function, mainly as a source of industrial raw materials and energy, both for domestic and export needs; and the mining business is able to play a role as the prime mover and spearhead of regional development, in addition to its role in fulfilling the livelihoods of the wider community (Hidjaz, 2019;Nguyen et al, 2020;Nguyen, 2020).…”
Section: Mining Activities In Indonesiamentioning
confidence: 99%
“…In contrast, listed time (AGE) has a negative relationship with the disclosure level of EAI of construction companies Liu and Anbumozhi (2009); Nguyen, Tran, Nguyen and Le (2017); Nguyen, Tran and Nguyen (2018); Nguyen, Le, and Pham (2018).…”
Section: Discussionmentioning
confidence: 96%
“…The findings showed that six factors affecting environmental accounting information disclosure in descending order as follows: (i) supervision of management agencies for environmental protection measures at enterprises, (ii) environmental accounting proficiency of accountants, (iii) attitudes of managers about environmental protection, (iv) guidelines for performing environmental accounting, (v) pressure from governments, importers, investors, financial institutions, communities on environmental information, and (vi) benefits of performing environmental accounting. Using data of 106 listed firms on the Vietnam stock market from three industries (forestry and fisheries, industry and construction, trade and services), Nguyen, Nguyen, Nguyen, Le, and Nguyen (2020) point out that EAI disclosure depends heavily on government regulations, then stakeholders pressure, view of company managers, firms size, community pressure, enterprises sector, profitability. Except for profits, the remaining variables positively impact on the disclosure of EAI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The less-informed or the uninformed party will suffer more damage than the informed party, and it leads to a conflict between the shareholders (the proxy) and the managers (the representative) (Juhmani, 2013 Furthermore, several studies examined factors related to firm characteristics that affect DISC. Barako (2007) (Nguyen et al, 2020b). No studies are currently examining the impact of firm characteristics on the DISC of 50 listed firms in Vietnam.…”
Section: Literature Reviewmentioning
confidence: 99%